Antibiotic Therapy in the Treatment of COVID-19 Pneumonia: Who and When? - Tat Ming Ng; Sean W. X. Ong; Audrey Y. X. Loo; Sock Hoon Tan; Hui Lin Tay; Min Yi Yap; David C. Lye; Tau Hong Lee; Barnaby E. Young (Antibiotics, 2022)
Background: COVID-19 imposes challenges in antibiotic decision-making due to similarities between bacterial pneumonia and moderate to severe COVID-19. We evaluated the effects of antibiotic therapy on the clinical outcomes of COVID-19 pneumonia patients and diagnostic accuracy of key inflammatory markers to inform antibiotic decision-making. Methods: An observational cohort study was conducted in patients hospitalised with COVID-19 at the National Centre for Infectious Diseases and Tan Tock Seng Hospital, Singapore, from January to April 2020. Patients were defined as receiving empiric antibiotic treatment for COVID-19 if started within 3 days of diagnosis. Results: Of 717 patients included, 86 (12.0%) were treated with antibiotics and 26 (3.6%) had documented bacterial infections. Among 278 patients with COVID-19 pneumonia, those treated with antibiotics had more diarrhoea (26, 34.7% vs. 24, 11.8%, p < 0.01), while subsequent admissions to the intensive care unit were not lower (6, 8.0% vs. 10, 4.9% p = 0.384). Antibiotic treatment was not independently associated with lower 30-day (adjusted odds ratio, aOR 19.528, 95% confidence interval, CI 1.039–367.021) or in-hospital mortality (aOR 3.870, 95% CI 0.433–34.625) rates after adjusting for age, co-morbidities and severity of COVID-19 illness. Compared to white cell count and procalcitonin level, the C-reactive protein level had the best diagnostic accuracy for documented bacterial infections (area under the curve, AUC of 0.822). However, the sensitivity and specificity were less than 90%. Conclusion: Empiric antibiotic use in those presenting with COVID-19 pneumonia did not prevent deterioration or mortality. More studies are needed to evaluate strategies to diagnose bacterial co-infections in these patients.